2014
DOI: 10.1371/journal.pone.0097181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In Vitro Exposure to Diarrheic Toxin Producer Prorocentrum lima on Gene Expressions Related to Cell Cycle Regulation and Immune Response in Crassostrea gigas

Abstract: Background Crassostrea gigas accumulates diarrheic shellfish toxins (DSP) associated to Prorocentrum lima of which Okadaic acid (OA) causes specific inhibitions of serine and threonine phosphatases 1 and 2A. Its toxic effects have been extensively reported in bivalve mollusks at cellular and physiological levels, but genomic approaches have been scarcely studied.Methodology/Principal FindingsAcute and sub-chronic exposure effects of P. lima were investigated on farmed juvenile C. gigas (3–5 mm). The Pacific oy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 56 publications
4
17
0
Order By: Relevance
“…The analysis of our results showed that the expression level in the studied genes was affected by cell concentration of the toxic dinoflagellates, as well as exposure time on C. gigas spat. These observations were consistent with those reported by other authors Romero-Geraldo & Hernández-Saavedra, 2014;García-Lagunas et al, 2013Romero-Geraldo et al, 2014, 2016. The expression level of cvt and lgbp gene showed a similar tendency, up-regulated for the three treatments at day three and down-regulated until the end of the experiment, indicating that DSP and PSP toxins inhibited the expression of these genes after five days of feeding.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…The analysis of our results showed that the expression level in the studied genes was affected by cell concentration of the toxic dinoflagellates, as well as exposure time on C. gigas spat. These observations were consistent with those reported by other authors Romero-Geraldo & Hernández-Saavedra, 2014;García-Lagunas et al, 2013Romero-Geraldo et al, 2014, 2016. The expression level of cvt and lgbp gene showed a similar tendency, up-regulated for the three treatments at day three and down-regulated until the end of the experiment, indicating that DSP and PSP toxins inhibited the expression of these genes after five days of feeding.…”
supporting
confidence: 92%
“…Paralytic shellfish toxins (PSTs) are a group of neurotoxic alkaloids, grouped into three structural families: carbamate (saxitoxin-STX, neosaxitoxin-NEO and gonyautoxins-GTX1 to GTX4), decarbamoyl and N-sulfocarbamoyl (Oshima, 1995). These dinoflagellate species have been associated with DSP and PSP episodes in different parts of the world, and in the Gulf of California, they have also been extensively used in aquatic toxicological studies (Pinto-Silva et al, 2005;Wikfors, 2005;Flórez-Barrós et al, 2011;García-Lagunas et al, 2013Romero-Geraldo et al, 2014, 2016.…”
mentioning
confidence: 99%
See 3 more Smart Citations